(untitled) (Research, Society and Development, 2021)
Food plays a fundamental role in the life of the human being, this work aims to understand school feeding via government purchases and the increase in the income of family farmers, contributing to strengthen the micro-economy of the municipality. The article was elaborated by means of a case study in the Rural Producers Association of the Micro watershed do Rio Branco (AMIBRA) in the municipality of Itanhaém - SP, where interviews of an exploratory and qualitative nature were carried out with the economic agents of the region, enabling the collection of data and information. In view of the above, the most relevant contribution was the finding that government purchases can be a new way of marketing agricultural products, which would result in the return of investments to the municipality and generate income that would boost the local economy. The expansion of the diversification and quantity of food produced by farmers for school meals in the municipality would foster the economy and improve the income of the community.